DASAR-DASAR MODERASI DALAM EPISTEMOLOGI PENDIDIKAN ISLAM PERSPEKTIF AL-QUR’AN - Kerwanto, Kerwanto (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
This article explores the principles of moderation extracted from the verses of the Qur'an which can be used as the basis for the epistemology of education in Islam. The important value of this study is the critique of the epistemology of modern Western education which ignores metaphysics as an approach and study in epistemology. Through this article, the author wants to show the basic nature of the reasoning of the Qur'an which gives balanced attention to human reality. The dimensions inherent in human reality- such as: exoteric-esoteric, physical-spiritual, individual (private)-social- are given attention by the Qur'an and placed in their respective positions. In this article, apart from discussing the reality of the human self from the perspective of the Al-Qur’an, the author also describes other themes, such as: the influence of morality, family and worship on education. Regarding the research approach, this article can be called a thematic interpretation study because the author tries to collect the verses of the Qur'an in a theme and then examines the interrelationships between these verses to produce a general concept.